Ibn Sina on Atomism: Translation of Ibn Sina's Kitab Al-Shifa, Al-Tabi'iyyat I: Al-Sama' Al-Tabi'i Third Treatise, Chapter 3-5 - Lettinck, Paul (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Ibn Sina on Atomism: Translation of Ibn Sina's Kitab Al-Shifa, Al-Tabi'iyyat I: Al-Sama' Al-Tabi'i Third Treatise, Chapter 3-5